Altlah dimensions of the phenomenon of metaphor in the Arabic language - yassmen, Ahmad; suleman , Abd AL- latef (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The reverse Stylistically event received considerable attention from the ancient and modern linguists because of generated from the energies of linguistic expression and creativity of thought beyond the mainstream and fashionable, and forms a metaphor based on the bypass typical literary expression, so it came this research to show the impact of the metaphor in the formation of the phenomenon of reverse dependent on the views of some linguists, and the search result that metaphor reverse based on breach uncommon in Sunan standard speech, which raises the recipient impressive including achieve characteristic aesthetic rhetorical, but it does not come out at all a departure from the grammar, but preferred creative pattern expressive on the other, as if the use of metaphor does not make it relevant germ of truth, but remain connected by an invisible bond of flour; because of which branch, and the branch does not understand only through the origin, but does not know it.